You're on the right track, but you made an error when you wrote out
4a+15 = -7
Instead it should be
-(4a+15) = -7
which is the same as
4a+15 = 7
This is because the "-(4a+15)*sqrt(3)" and "-7sqrt(3)" terms both start with a negative. Solving 4a+15 = 7 leads to a = -2
Use a = -2 and you should get b = 2
-------------------------------------------------------------
Check:
Plug in a = -2 into the LHS and compute
(4-3*sqrt(3))*(5-a*sqrt(3)) = (4-3*sqrt(3))*(5+2*sqrt(3)) = -10.1243556529821
plug b = 2 into the RHS and compute
b - 7*sqrt(3) = 2 - 7*sqrt(3) = -10.1243556529821
we get the same approximate value on each side, so LHS = RHS when a = -2 and b = 2.